2017
DOI: 10.1093/jamia/ocx074
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of acute care patient portals: recommendations on utility and use from six early adopters

Abstract: We summarize the experiences of 6 organizations that have implemented acute care portals, representing a variety of settings and technologies. We discuss the considerations for and challenges of incorporating various features into an acute care patient portal, and extract the lessons learned from each institution's experience. We recommend that stakeholders in acute care patient portals should: (1) consider the benefits and challenges of generic and structured electronic care team messaging; (2) examine strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 41 publications
0
51
0
Order By: Relevance
“…12,13 The increasing popularity of portals and their potential utility to hospitalized patients has motivated some organizations to adopt inpatient portals, or patient portals accessed in the hospital setting. [14][15][16][17][18][19] Vendors now offer portals intended specifically for in-hospital use, such as MyChart Bedside from Epic Systems Corporation. 20 Institutions use inpatient portals to address patients' information needs, engage patients in decision making, facilitate patient-provider communication, improve transparency, provide health education, increase patient safety, and enable transitions of care.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…12,13 The increasing popularity of portals and their potential utility to hospitalized patients has motivated some organizations to adopt inpatient portals, or patient portals accessed in the hospital setting. [14][15][16][17][18][19] Vendors now offer portals intended specifically for in-hospital use, such as MyChart Bedside from Epic Systems Corporation. 20 Institutions use inpatient portals to address patients' information needs, engage patients in decision making, facilitate patient-provider communication, improve transparency, provide health education, increase patient safety, and enable transitions of care.…”
Section: Background and Significancementioning
confidence: 99%
“…20 Institutions use inpatient portals to address patients' information needs, engage patients in decision making, facilitate patient-provider communication, improve transparency, provide health education, increase patient safety, and enable transitions of care. 14,15 Research suggests that inpatient portals may improve patient safety and satisfaction. [21][22][23][24][25][26] Inpatient portals empower patients to report safety concerns, facilitate patient recognition of errors, improve patients' perceptions of safety and quality, and fulfill patients' information needs.…”
Section: Background and Significancementioning
confidence: 99%
“…Two studies used questionnaires [17,18]; four used interviews or focus groups [19][20][21][22][23][24]; two used mixed methods [25,26]. One note analysis, [27] one portal analysis [28] and one clinical trial [29,30] was conducted, and six analysis articles were identified [31][32][33][34][35][36]. One empirical study came from each of Israel [19], Norway [20,21] and Canada [18]; the rest originated from the USA.…”
Section: Resultsmentioning
confidence: 99%
“…Sharing notes was seen to empower patients by improving trust and knowledge [30], facilitating patients to work with doctors [28]. Communication of written information was considered superior to verbal explanations; one patient was reported as saying "Yeah, they come and update me but..I mean I can't keep track of it all.…”
Section: Impact On Patient Carementioning
confidence: 99%
See 1 more Smart Citation